Central nervous system activities of extract Mangifera indica L. (5th October 2020) - López-Ríos, Laura; Wiebe, Julia C; Vega-Morales, Tanausú; Gericke, Nigel
Abstract: Ethnobotanical relevance: Leaves of Mangifera indica L. have folk-uses in tropical regions of the world as health teas, as a remedy for exhaustion and fatigue, as a vegetable, and as a medicine. Mangifera indica leaf extract (MLE) had previously been demonstrated to alter brain electrical activity in-vivo. The aim of the present series of studies was to investigate whether mangiferin, a major compound in leaves and in MLE, is responsible for the neurocognitive activity of MLE, and if the CNS activities of MLE have translational potential. Materials and methods: MLE, tradename Zynamite, is produced by Nektium Pharma, Spain. Isolated mangiferin was tested in-vitro in radioligand binding and enzyme inhibition studies against 106 CNS targets. Changes in the electroencephalograms (EEG's) of MLE and mangiferin were recorded in-vivo from four brain regions. Two double blind randomized placebo-controlled crossover clinical trials were conducted, each with 16 subjects. At 90 min and at 60 min respectively, after oral intake of 500 mg MLE, EEG recordings, psychometric tests, mood state, and tolerability were studied. Results: Isolated mangiferin is a selective inhibitor of catechol-O-methyltransferase (COMT) with an IC50 of 1.1 μM, with no activity on the CNS targets of caffeine. Both mangiferin and MLE induce similar changes in long-term potentiation (LTP) in the hippocampus in-vitro, and induce a similar pattern of EEG changes in-vivo. In both translational clinical trials MLE was well tolerated, with no cardiovascular side-effects. In both studies MLE caused significant spectral changes in brain electrical activity in cortical regions during cognitive challenges, different to the attenuated spectral changes induced by caffeine. There were no significant changes in the psychometric tests other than reaction time for all groups. In the second study there was a trend to faster reaction time within group for MLE (p = 0.066) and the percentage improvement in reaction time for MLE compared to placebo was significant (p = 0.049). In the first study MLE improved all scores for Profile of Mood States (POMS), with the score for "fatigue" significantly improved (p = 0.015); in the second study the POMS score for "dejection" was improved in the caffeine group, p = 0.05. Conclusions: Mangiferin is a COMT inhibitor of moderate potency and is the major CNS-active compound in MLE. Both mangiferin and MLE increase hippocampal LTP in-vitro, and induce a similar pattern of changes in brain electrical activity in-vivo. While the translational clinical trials of MLE are limited by being single dose studies in a small number of subjects, they provide the first clinical evidence that the extract is well tolerated with no cardiovascular side-effects, can induce changes in brain electrical activity, may give a faster reaction time, and decrease fatigue. These CNS activities support the reported folk-uses use of mango leaf tea as a substitute for tea and as a traditional remedy for fatigue and exhaustion. Extract Mangifera indica L., Zynamite, has nootropic potential, and larger clinical studies are needed to realise this potential. Graphical abstract: Image 1 Highlights: Mangiferin was found for the first time to be a catecho-O-methyltransferase inhibitor. Mangiferin and Mangifera indica extract (MLE Zynamite) for the first time have been shown to increase long-term potentiation. Mangiferin and Zynamite have shown to cause a similar pattern of change in EEG in vivo. In clinical trials Zynamite improved brain activity, reaction time, fatigue, but didn't affect blood pressure and heart rate.